Multiple Intelligences of Students in SMAN 1 V Koto Kampung Dalam Padang Pariaman - Rizki Rahman Putra; Rahmadhani Fitri; Indra Hartanto; Ganda Hijrah Selaras (Universitas Negeri Padang, 2020)
Multiple Intelligences (MI) is a theory about intelligence that was triggered by Dr. Howard Gardner, a figure in education and psychology. Multiple Intelligences consist of linguistic intelligence, logic-mathematical intelligence, visual-spatial intelligence, gesture intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, naturalist intelligence. Everyone has MI at different levels. Therefore, each teacher should be able to understand the intelligence and abilities of each student well, this is because the conditions of students in the class are different and have different levels of intelligence. This is in accordance with the role of the teacher as a motivator, facilitator, and director. Many benefits can be obtained by knowing the level of MI of students, both for schools and for students themselves. some of the benefits of MI for students and schools, for students if the MI level is known it can increase their self-confidence and help students to choose majors. For schools the level of MI that students have can help teachers focus more on the learning process, helping to group students, can approach students according to the type of intelligence they have. In addition, by knowing the level of MI of students, teachers can develop optimally the potential that exists in students and can choose the right strategy in the learning process. From the results of observations at SMAN 1 V Koto Kampung Dalam Padang Pariaman it can be seen that there is no meaningful relationship between the MI overall and MI partially with the learning outcomes